Shape memory properties and oxidation behaviour of a rapidly liquid quenched Cu-Sn alloy - Ceylan, M; Zengin, R (Elsevier Science Sa, 2000)
Rapidly liquid quenched Cu-Sn ribbons were produced and their shape memory properties and oxidation behaviour investigated using thermal analysis, metallography and X-ray diffraction methods. During the heating regime from -70 degrees C to room temperature in a DSC instrument, martensite --> austenite transformation was performed and the A(s) and A(f) temperatures were determined as - 16.4 degrees C and -8.4 degrees C respectively. The oxidation behaviour was also determined using TGA. The total oxidation percentages decreased with increasing heating rate, whereas the oxidation rate increased with the heating rate during the heating and cooling times. The shape memory behaviour of the ribbon samples were also seen after bending in liquid nitrogen and reheating to room temperature. (C) 2000 Elsevier Science S.A. All rights reserved.